Biological and immunological properties of the HMB-2 human melanoma cell line - Svec, J; Veselovská, Z; Keszeghová, V; Matoska, J; Marchetti, A; Squartini, F (Neoplasma, 1988)
The HMB-2 human melanoma cell line derived from a lymph node metastatis is described. After long-term cultivation in vitro the cells retained their morphology, high growth rate, xenotransplantability into immunosuppressed mice and genotypic and phenotypic markers of human melanoma cells. Upon infection of the HMB-2 cells with temperature-sensitive mutant vesicular stomatitis virus (VSVts045) at nonpermissive temperature, a complemented virus pseudotype (VSV(HMB-2] was produced carrying assembled melanoma-associated antigens. Monoclonal antibodies prepared against HMB-2 cell membrane proteins and proteins of purified VSV(HMB-2) particles showed different reactivity with various human tumor cell lines and tissues: While the RG-12 anti-HMB-2 monoclonal antibody recognized a class II tumor-associated antigen present in melanoma and carcinoma tissues, the B-6 anti-VSV(HMB-2) antibody showed selective reactivity with melanoma cells.
Keywords: nádorové buňky kultivované; buněčné linie; ženské pohlaví; lidé; karyotypizace; myši; Transplantation, Heterologous; Neoplasm Transplantation; Melanoma; buněčné dělení; Cell Line; Mice; Cell Division; Tumor Cells, Cultured; lidé středního věku; Enzyme-Linked Immunosorbent Assay; Animals; radioimunoanalýza; Lymphatic Metastasis; transplantace heterologní; Mice, Inbred CBA; Humans; Radioimmunoassay; Immunoenzyme Techniques; lymfatické metastázy; imunoenzymatické techniky; ELISA; zvířata; melanom; nádorové proteiny; myši inbrední CBA; Karyotyping; Neoplasm Proteins; Middle Aged; transplantace nádorů; Female